2001
DOI: 10.1093/bja/87.3.400
|View full text |Cite
|
Sign up to set email alerts
|

Cross-validation of a composite pain scale for preschool children within 24 hours of surgery

Abstract: This study was designed to cross-validate a composite measure of the pain scales CHEOPS (Children's Hospital of Eastern Ontario Pain Scale), OPS (Objective Pain Scale, simplified for parent use by replacing blood pressure measurement with observation of body language or posture), TPPPS (Toddler Preschool Postoperative Pain Scale) and FLACC (Face, Legs, Activity, Cry, Consolability) in 167 Thai children aged 1-5.5 yr. The pain scales were translated and tested for content, construct and concurrent validity, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
86
0
8

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(96 citation statements)
references
References 16 publications
2
86
0
8
Order By: Relevance
“…We used both the faces and CHEOPS pain scales to cross-validate the results, especially in the PACU. 18 We used a visual analogue scale on the ward as it is more sensitive than simple descriptive scales and can be used in children four to five years old. We found that preoperative dexamethasone administration improves pain scores, reduces analgesic requirements, allows earlier oral fluid intake, and improves postoperative swallowing and the quality of oral intake.…”
Section: Figure 1 Median Children's Hospital Eastern Ontario Painmentioning
confidence: 99%
“…We used both the faces and CHEOPS pain scales to cross-validate the results, especially in the PACU. 18 We used a visual analogue scale on the ward as it is more sensitive than simple descriptive scales and can be used in children four to five years old. We found that preoperative dexamethasone administration improves pain scores, reduces analgesic requirements, allows earlier oral fluid intake, and improves postoperative swallowing and the quality of oral intake.…”
Section: Figure 1 Median Children's Hospital Eastern Ontario Painmentioning
confidence: 99%
“…7 The TPPPS, in turn, is a scale that can be used to assess pain during and after medical or surgical procedures, on the basis of behavioral indicators. 8,9 In the remainder of the studies, the majority of the instruments whose psychometric qualities were being assessed used ordinal scales, i.e., they categorize attributes and establish a sequential order based on the characteristics of the attribute measured. 6 It should be pointed out that, although ordinal scales are less precise than interval scales, they are generally used with children to obtain self-reported pain assessments since they are easier for children to understand, as is the case of the Oucher Faces Scale, 10 the Faces Pain Scale (FPS) 11,12 and the Facial Affective Scale (FAS).…”
Section: Measurement Scales Of the Instruments Analyzedmentioning
confidence: 99%
“…11 Nevertheless, in the course of this literature review it was found that ordinal scales are also used by trained observers or by the medical and nursing teams to assess child pain. In these cases the following instruments were used: the Objective Pain Scale (OPS), 8 the Faces, Leg, Activity, Cry and Consolability scale (FLACC), 8,[13][14][15] the Children's Hospital of Eastern Ontario Pain Scale (CHEOPS), 8 the Pediatric Pain Profile (PPP), 16 the Alder Hey Triage Pain Score (AHTPS), 17 the Child Facial Coding System (CFCS) 18 and the Non-Communicating Children's Pain Checklist-Revised (NCCPC-R). 19 …”
Section: Measurement Scales Of the Instruments Analyzedmentioning
confidence: 99%
See 2 more Smart Citations